2007
DOI: 10.1051/0004-6361:20066295
|View full text |Cite
|
Sign up to set email alerts
|

Asteroseismology of the PG 1159 star PG 0122+200

Abstract: Context. The variable pre-white dwarf PG 1159 stars (GW Vir) are g-mode non-radial pulsators. Asteroseismology puts strong constraints on their global parameters and internal structure. PG 0122+200 defines the red edge of the instability strip and its evolutionary timescale is predicted to be dominated by neutrino emission. Its study offers the opportunity to better understand the instability mechanism and to validate the physics of the neutrino production in dense plasma. Aims. To achieve such a goal requires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…References. -(0) This work; (1) Giammichele et al (2016); (2) Dolez et al (2006); (3) Fu et al (2013); (4) Su et al (2014); (5) Pfeiffer et al (1996); (6) Bognár et al (2016); (7) Bradley (2001); (8) Castanheira et al (2013); (9) Kepler et al (1995); (10) Pech & Vauclair (2006); (11) Fu et al (2007); (12) Bond et al (1996); (13) Charpinet et al (2009); (14) Vauclair et al (2002); (15) Kawaler et al (1995); (16) Østensen et al (2011); (17) Hermes et al (2017b); (18) Bell et al (2015); (19) Greiss et al (2014); (20) icantly simplifies mode identification and affords us the opportunity to probe internal rotation for 20 of the 27 DAVs we present here. For example, Figure 1 shows the five dipole (ℓ = 1) modes in EPIC 201802933 (SDSSJ1151+0525) identified from their splittings.…”
Section: Rotation Ratesmentioning
confidence: 99%
“…References. -(0) This work; (1) Giammichele et al (2016); (2) Dolez et al (2006); (3) Fu et al (2013); (4) Su et al (2014); (5) Pfeiffer et al (1996); (6) Bognár et al (2016); (7) Bradley (2001); (8) Castanheira et al (2013); (9) Kepler et al (1995); (10) Pech & Vauclair (2006); (11) Fu et al (2007); (12) Bond et al (1996); (13) Charpinet et al (2009); (14) Vauclair et al (2002); (15) Kawaler et al (1995); (16) Østensen et al (2011); (17) Hermes et al (2017b); (18) Bell et al (2015); (19) Greiss et al (2014); (20) icantly simplifies mode identification and affords us the opportunity to probe internal rotation for 20 of the 27 DAVs we present here. For example, Figure 1 shows the five dipole (ℓ = 1) modes in EPIC 201802933 (SDSSJ1151+0525) identified from their splittings.…”
Section: Rotation Ratesmentioning
confidence: 99%
“…The resulting averaged rotational splitting of 3.405 μHz translates into an average rotation period of 1.70 days. This is a slightly longer rotation period than the 1.55 days found by Fu et al (2007). In addition, the nonlinear effect invoked by Goupil et al (1998) also implies a time modulation of the departure to equal splitting within the triplets in the intermediate regime.…”
Section: Rotational Splitting Revisitedmentioning
confidence: 65%
“…Those frequencies are seen in the power spectrum of all the timeseries. We interpret the 1558.671 μHz (641.6 s period) as a component of one additional = 1 mode to the series listed in Fu et al (2007) in which the lowest frequency mode was at 1636.25 μHz (611.15 s). This new mode corresponds to the k = 25 order, = 1 mode of the best-fit model of Córsico et al (2007), which is found at 633.1 s; however, we detect only one frequency, so we do not know its m value.…”
Section: Results Of the 2005 And 2008 Multisite Campaignsmentioning
confidence: 91%
See 2 more Smart Citations